The role of social isolation stress in escalated aggression in rodent models - Aki Takahashi (Neuroscience Research)
Anti-social behavior and violence are major public health concerns. Globally, violence contributes to more than 1.6 million deaths each year. Previous studies have reported that social rejection or neglect exacerbates aggression. In rodent models, social isolation stress is used to demonstrate the adverse effects of social deprivation on physiological, endocrinological, immunological, and behavioral parameters, including aggressive behavior. This review summarizes recent rodent studies on the effect of social isolation stress during different developmental periods on aggressive behavior and the underlying neural mechanisms. Social isolation during adulthood affects the levels of neurosteroids and neuropeptides and increases aggressive behavior. These changes are ethologically relevant for the adaptation to changes in local environmental conditions in the natural habitats. Chronic deprivation of social interaction after weaning, especially during the juvenile to adolescent periods, leads to the disruption of the development of appropriate social behavior and the maladaptive escalation of aggressive behavior. The understanding of neurobiological mechanisms underlying social isolation-induced escalated aggression will aid in the development of therapeutic interventions for escalated aggression.